Інвестиційна привабливість туристичної інфраструктури України: аналітичний аспект - Кукіна, Наталя Володимирівна; Тараненко, Галина Григорівна; Kukina, Natalia; Taranenko, Halyna (Запоріжжя : 2022, 2022)
UA: У статті зроблено аналіз інвестиційної привабливості туристичної інфраструктури України. За допомогою методики інтегральних індексів показників інфраструктури внутрішнього туризму та інвестиційної привабливості галузі складено матрицю потенціалу регіональної туристичної інфраструктури, розроблено рекомендації по напрямку інвестицій в інфраструктуру регіонів. EN: In today's economic conditions, the main directions of the investment strategy for the development of the tourism industry should be intensive capital investments in the improvement of the old and the development of new infrastructure, which guarantees the competitiveness of Ukraine on the domestic and global markets of tourist services. In this regard, in order to attract investments in the development of tourism infrastructure, it is necessary to launch organizational and economic mechanisms that stimulate the investment attractiveness of the industry. The primary condition for the creation of an effectively functioning system of investment processes in the tourism industry is the study of the state and determination of the main trends in the infrastructure of the tourism industry based on the analysis of the characteristics of the factors and directions of the development of investment processes in this industry. Аn assessment of the investment attractiveness of the tourist industry of the regions of Ukraine was carried out, depending on the level of development of the regional infrastructure. Form a map of the regional level of development of tourist infrastructure for the period 2015-2020. On the basis of the configuration matrix of the portfolio analysis, the optimal directions of investment in the tourist infrastructure of the regions were developed. It was determined that 12 out of 24 regions of Ukraine have a low level of tourist infrastructure. This allows us to state the presence of a disproportion in the distribution of investments and state subsidies between regions regarding the development of the tourism industry in the country. A high level of tourism infrastructure development is characteristic only of Kyiv, Lviv, Odesa and Dnipropetrovsk regions. The established dependence of tourist infrastructure on investment attractiveness showed that the domestic tourism segment of absolutely all regions needs financing from investors and the state. However, it will be effective only under the conditions of elimination of the disparity in the development of territories by implementing the appropriate type of investment policy for a separate region.
Investment attractiveness of tourist infrastructure of Ukraine: analytical aspect
Keywords: інвестиції; інвестиційна привабливість; інфраструктура туризму; розвиток; тип інвестиційної політики; туристична галузь; investment; investment attractiveness; tourism infrastructure; development; type of investment policy; tourism industry